Where is clear aligner therapy research heading? - Ruşen Erdem; Yavuz Selim Genç; Burkay Moroğlu; Nurbanu Moroğlu; Ahmet Yıldırım (Clinical Dentistry and Research, 2026)
Background and Aim: The aim of this study was tosystematically identify the core themes, research trends, andunderexplored topics in the clear aligner literature by employinga natural language processing-based topic modeling approachusing the BERTopic algorithm.Materials and Methods: Publications on clear alignertherapy published between 2015 and 2025 and indexed inthe Scopus database were retrieved by searching the title,abstract, and author keywords using the terms “clear aligner*”and “invisalign*.” After restricting publication types, applyingthe English language filter, and removing records with missingmetadata, a final dataset of 1,323 publications was obtained.The retrieved data were merged, preprocessed, and analyzedusing the BERTopic algorithm to identify thematically coherentclusters and evaluate topic trends over time.Results: A total of 1,323 publications were analyzed, revealingdistinct thematic clusters. “Mechanical and Surface Propertiesof Dental Materials” emerged as the most frequently publishedtopic, while “FEM Analysis of Maxillary Molar Distalization” and“Bond Strength and Surface Wear of Composite Attachments”demonstrated statistically significant positive annual trendcoefficients (p < 0.05), indicating their emergence as currenthot topics. China, Italy, and the United States ranked as the topthree most productive countries.Conclusions: This study analyzed the clear aligner literaturepublished between 2015 and 2025 using a BERTopic-basedtopic modeling approach, revealing thematic priorities, researchtrends, and geographical patterns in the field. These findingssuggest that advancements in clear aligner therapy are largelydriven by innovations in materials science, developments indigital orthodontic technologies, and evolving clinical demands.